A New Species of the Genus Zhangixalus (Amphibia: Rhacophoridae) from Vietnam - NINH, Hoa Thi; NGUYEN, Tao Thien; ORLOV, Nikolai; NGUYEN, Truong Quang; ZIEGLER, Thomas (European Journal of Taxonomy, 2020)
We describe a new species of the genus Zhangixalus Li, Jiang, Ren & Jiang, 2019 from Ha Giang Province, Vietnam based on morphological and molecular data. In the molecular phylogenetic analyses, the new species is nested in the Zhangixalus duboisi (Ohler, Marquis, Swan & Grosjean, 2000) group, where it is sister to Z. duboisi with a genetic distance of 2.51%. The new species, Zhangixalus franki sp. nov., differs from its congeners by a combination of the following morphological characters: size large, SVL 77.9–85.8 mm in males; finger webbing formula I1-1II0-1III½-0IV; dorsal surface of head and body green with dark brown spots; ventral surface grey or dark grey, white stripe along edge of jaw, insertion of limbs, and along lateral ridges of fore and hind limbs and flank, separating upper green part from lower grey part. The new species occurs in evergreen montane tropical forests at an elevation of ca 1300 m a.s.l. The new discovery brings the total number of known species in the genus Zhangixalus to 38 and the species number reported from Vietnam to nine.